2015
DOI: 10.1152/ajpheart.00162.2015
|View full text |Cite
|
Sign up to set email alerts
|

In vitro particulate matter exposure causes direct and lung-mediated indirect effects on cardiomyocyte function

Abstract: Particulate matter (PM) exposure induces a pathological response from both the lungs and the cardiovascular system. PM is capable of both manifestation into the lung epithelium and entrance into the bloodstream. Therefore, PM has the capacity for both direct and lung-mediated indirect effects on the heart. In the present studies, we exposed isolated rat cardiomyocytes to ultrafine particulate matter (diesel exhaust particles, DEP) and examined their contractile function and calcium handling ability. In another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 53 publications
(55 reference statements)
2
16
0
Order By: Relevance
“…Huang et al (Huang et al 2010) demonstrated that acute exposure to DE particles by intra-tracheal instillation produced significant myocardial dysfunction in rats, including decreased left ventricular systolic and diastolic contractility. In addition, exposure to DE particles in vitro resulted in cardiomyocyte contractile dysfunction and reduced calcium handling (Gorr et al 2015). In agreement with these studies, our study found that DE exposure reduced cardiac function and cardiac contractility in isolated perfused hearts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Huang et al (Huang et al 2010) demonstrated that acute exposure to DE particles by intra-tracheal instillation produced significant myocardial dysfunction in rats, including decreased left ventricular systolic and diastolic contractility. In addition, exposure to DE particles in vitro resulted in cardiomyocyte contractile dysfunction and reduced calcium handling (Gorr et al 2015). In agreement with these studies, our study found that DE exposure reduced cardiac function and cardiac contractility in isolated perfused hearts.…”
Section: Discussionsupporting
confidence: 91%
“…The pro-redox components of DE may modulate cardiomyocyte calcium regulation by reducing intracellular calcium or changing sensitivity of contractile proteins to calcium, resulting in diminished cardiac contractility. Gorr et al (Gorr et al 2015) demonstrated that reduced calcium handlings from DE treatment in cardiomyocytes was mediated by cellular oxidative stress. The preserved contractility during reperfusion in hearts exposed to fresh DE could indicate altered intracellular Ca 2+ regulation in the myocardium.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, there are some reports that the cardiac effects by DEP, especially arrhythmia, have been attributed to changes in autonomic activity that was not present in cells [41]. However, there are other recent data supporting our results that PM can cross into the pulmonary and systemic circulations directly affecting the heart and blood vessels [42] and DEP has shown both direct and indirect effects on cardiomyocyte functions [43]. The electrophysiological instability by PM or PAHs was completely blocked by pretreatment of the cells with an ROS scavenger, which is consistent with a recent study that revealed that the arrhythmogenic effects induced by DEP were prevented by antioxidant treatment and a CaMKII blockade [9].…”
Section: Discussionsupporting
confidence: 82%
“…There is also substantial evidence suggesting a positive correlation between particulate air pollution exposure and adverse cardiovascular outcomes during the postnatal periods 9, 10 . In another study, cardiomyocytes cultured in media from PM-treated lung epithelial cells demonstrated contractile dysfunction 11 . The multitude of PM 2.5 effects (both direct and indirect) on the cardiovascular system are also well reviewed by others 12, 13 These studies are suggestive that PM 2.5 exposure is associated with critical biological and cardio-developmental mechanisms leading to harmful effects later in life.…”
Section: Introductionmentioning
confidence: 96%